Making Reintegration Work for Youth in Northern Uganda - Annan, Jeannie; Blattman, Chris; Carlson, Khristopher; Mazurana, Dyan (Tufts Archival Research Center, 2005)
New survey data on war-affected youth suggest that past approaches and programs are insufficient to meet the needs of youth newly returning from the Lord's Resistance Army (LRA) as well as those who have already returned.